The effect of a long-term treatment with cannabidiol-rich hemp extract oil on the adenosinergic system of the zucker diabetic fatty (ZDF) rat atrium - Viczjan, Gabor; Szilagyi, Anna; Takacs, Barbara; Ovari, Ignac; Szekeres, Reka; Tarjanyi, Vera; Erdei, Tamas; Teleki, Vanda; Zsuga, Judit; Szilvassy, Zoltan; Juhasz, Bela; Varga, Balazs; et al. (Frontiers in Pharmacology, 2022)
Cannabidiol (CBD), the most extensively studied non-intoxicating phytocannabinoid, has been attracting a lot of interest worldwide owing to its numerous beneficial effects. The aim of this study was to explore the effect that CBD exerts on the adenosinergic system of paced left atria isolated from obese type Zucker Diabetic Fatty (ZDF) rats, maintained on diabetogenic rat chow, received 60 mg/kg/day CBD or vehicle via gavage for 4 weeks. We found that N6-cyclopentyladenosine (CPA), a relatively stable and poorly transported A1 adenosine receptor agonist, elicited a significantly weaker response in the CBD-treated group than in the vehicle-treated one. In contrast, adenosine, a quickly metabolized and transported adenosine receptor agonist, evoked a significantly stronger response in the CBD-treated group than in the vehicle-treated counterpart (excepting its highest concentrations). These results can be explained only with the adenosine transport inhibitory property of CBD (and not with its adenosine receptor agonist activity). If all the effects of CBD are attributed to the interstitial adenosine accumulation caused by CBD in the myocardium, then a significantly increased adenosinergic activation can be assumed during the long-term oral CBD treatment, suggesting a considerably enhanced adenosinergic protection in the heart. Considering that our results may have been influenced by A1 adenosine receptor downregulation due to the chronic interstitial adenosine accumulation, an adenosinergic activation smaller than it seemed cannot be excluded, but it was above the CBD-naïve level in every case. Additionally, this is the first study offering functional evidence about the adenosine transport inhibitory action of CBD in the myocardium.